Considerations for the transportation of school aged children amid the Coronavirus pandemic. (March 2021) - Abulhassan, Yousif; Davis, Gerard A.
Highlights: Anthropometry of children should be considered in virus control countermeasures. A bus monitor is necessary to ensure passenger compliance with countermeasures. Physical distancing on school buses may not be feasible on school buses. A systematic approach is necessary when implementing change to school bus cabins. Abstract: Close proximity seating and the distinctive anthropometric characteristics of young children introduce unique challenges when implementing control strategies to promote safe transportation on school buses. Though face coverings may become one of the most commonly used controls on mass transportation to reduce the spread of COVID-19, the lack of personal protective equipment specifically designed for young children requires further investigation into control strategies to potentially reduce the spread of COVID-19 among school bus passengers. The purpose of this paper is to identify potential concerns and countermeasures (immediate and long term) to be considered for the safe transportation of children amid the Coronavirus (COVID-19) crisis by taking into consideration the design of school bus cabins and the anthropometric characteristics of children. COVID-19 mitigation strategies concerning cabin design and busing operations are discussed to provide general recommendations for operating fleets while providing as safe and healthy a passenger environment as possible considering both practicality and cost-effectiveness. The risk of virus transmission among school bus passengers may be reduced by adhering to Centers for Disease Control and Prevention (CDC) guidelines, and additional bus specific considerations such as structured loading and unloading criteria, face coverings guidelines, incorporation of a bus monitor, and potential modifications/design changes for existing/future school buses. Several controls being used to protect passengers from virus transmission in other modes of mass transportation could also have the potential for immediate incorporation into school buses.